صكوك المضاربة وتطبيقاتها في المصارف الإسلامية - بجيتش، محمد بن عصمت (Kulliyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2005)
This thesis focuses on a modern Islamic investment instrument named "sukuk of mudarabah". It is an effective way of developing of traditional transaction of "mudarabah", making it more suitable for contemporary lifestyle. At the beginning of the thesis the researcher has discussed the meaning of the term "mudarabah", its conditions, method of distribution of profit and termination of the contract. Subsequently, he has discussed the effective implementation of "mudarabah" in Islamic banks. After this, he has explained the theoretical side of "sukuk of mudarabah": definition of the term of "sukuk of mudarabah" and its legal forming, ruling and components in Islamic law. Additionally, he has put his attention on the rules of Guarantee, transfer and termination of "sukuk". The practical part of the thesis has discussed two experiments: Jordanian and Malaysian in terms of practical implementation of "sukuk of mudarabah" by utilizing analytical and critical approaches. The researcher has utilized the inductive method in order to gather information from the resources, and analytical and comparative methods in order to analyze the views of scholars concerning the topic and compare among these views. The researcher has concluded that both Jordanian and Malaysian experiments have failed in issuing "sukuk" based on "mudarabah", because both of them are based on contract of "qard", and contain forbidden profit gained through usury.